Clinical Efficacy of Doxycycline for Treatment of Macrolide-Resistant Mycoplasma pneumoniae Pneumonia in Children - Hyunju Lee; Youn Young Choi; Young Joo Sohn; Ye Kyung Kim; Mi Seon Han; Ki Wook Yun; Kyungmin Kim; Ji Young Park; Jae Hong Choi; Eun Young Cho; Eun Hwa Choi (MDPI AG, 2021)
In areas with high prevalence of macrolide-resistant Mycoplasma pneumoniae (MRMP) pneumonia, treatment in children has become challenging. This study aimed to analyze the efficacy of macrolides and doxycycline with regard to the presence of macrolide resistance. We analyzed children with MP pneumonia during the two recent epidemics of 2014-2015 and 2019-2020 from four hospitals in Korea. Nasopharyngeal samples were obtained from children with pneumonia for MP cultures and polymerase chain reaction (PCR). Macrolide resistance was determined by the analysis of 23S rRNA gene transition. Time to defervescence and to chest X-ray improvement were analyzed. Of 145 cases, the median age was 5.0 years and MRMP accounted for 59 (40.7%). Among macrolide-susceptible MP (MSMP), 78 (90.7%) were treated with macrolides and 21 (35.6%) in the MRMP group with doxycycline. In MRMP pneumonia, shorter days to defervescence (2 vs. 5 days, p < 0.001) and to chest X-ray improvement (3 vs. 6 days, p < 0.001) in the doxycycline group than in the macrolide group was observed, whereas no differences were observed among children with MSMP pneumonia. Compared to macrolides, treatment with doxycycline resulted in better outcomes with a shorter time to defervescence and to chest X-ray improvement among children with MRMP pneumonia.